HOW TO STRUCTURE A KNOWLEDGE-SHARING PROCESS BASED ON DIFFERENT CONFIGURATIONS OF TIME AND SPACE DIMENSIONS: A DIGITAL LITERACY PERSPECTIVE : :a digital literacy perspective - Evangelista Silva, Sergio; Almeida de Oliveira, Renan; Ragi Curi Filho, Wagner (Revista Conhecimento Online: Diversidade e Inclusão Social, 2022)
The availability and progress of information and communication technologies opened new possibilities for learning processes. Even though there are recent studies about the use of technologies in learning processes, a more systematic and deep debate about the forms of knowledge sharing in teaching processes and how technologies can be used in different educational contexts is still necessary. This paper investigates forms of knowledge sharing used in an education setting and introduces a method to the analysis of the knowledge sharing process based on four possible configurations of knowledge sharing (same-time same-place, same-time different-place, different-time same-place, different-time different-place) under the perspective of digital literacy. As the study object, teachers of an engineering course were interviewed with respect to the pedagogical practices adopted in the context of the Covid-19 Pandemic and the feasibility of continuing some of them after this period. The coding of these experiences and the reflection on them permitted the introduction of a framework for the structuration of knowledge-sharing practices in educational environments that employ different configurations of space-time in the educational process, under the conceptual lenses of digital literacy. This method seems to be a feasible tool for analysis of different situations where there are different practices of knowledge sharing.